Performa Support Vector Machine Pada Klasifikasi Lahan dan Air Tanah - Angellina Angellina; Dyah Erny Herwindiati; Janson Hendryli (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
Groundwater is one of the sources of water in the world. The availability of groundwater is one of the factors that plays an important role in carrying out daily life activities, including for drinking, cooking, washing, irrigating rice fields, and many others. One source of groundwater in Jakarta is obtained from the Ciliwung River which is passed by the Bogor and Depok areas. However, the existence of springs and groundwater continues to decrease until now. The purpose of this paper is to discuss the first stage of the classification of groundwater availability in several sub-districts in the Bogor and Depok areas. The results of phase one will present a mapping of green areas along with their classification. Data taken from Landsat 8 Satellite Imagery - United States Geological Survey (USGS). The Support vector Machine (SVM) method is used to classify the availability of groundwater. The input data for the training process are the Normalized Difference Vegetation Index, Soil Adjusted Vegetation Index, and Enhanced Vegetation Index constants. The results of the evaluation using linear kernel produced a green F1 score of 89.58%, half green 65.62%, and dry 83.44%. While the results of the evaluation using the polynomial kernel produced a green F1 score of 83.58%, half green 25.68%, and dry 66.59%.